Analisis Kaidah al-Masyaqqah Tajlibu al-Taysir dalam Aktivitas Ekonomi Masyarakat - Reza Arifayanti; Shafinatun najah (HOKI : Journal of Islamic Family Law, 2026)
This article examines the fiqh principle Al-Masyaqqah Tajlibu at-Taysīr and its relation to community economic activities within the framework of Islamic economics, as stated in Qur'an Surah Al-Baqarah: 185. This study aims to analyze the concept of this principle and its implementation in daily economic activities. The method used is a qualitative approach through a literature study based on the Qur'an, Hadith, classical Islamic texts, and relevant academic journals. The findings show that this principle provides ease in various economic activities such as financial transactions and muamalah practices, especially under difficult or emergency conditions. However, its application is not absolute, as it must fulfill specific shar’iyyah requirements to prevent misuse. Therefore, a proper understanding of this principle is essential in maintaining a balance between flexibility and the provisions of Islamic law in community economic life.